Upaya Guru IPS dalam Menanamkan Nilai-Nilai Moral pada Siswa SMP Negeri 2 Sumbergempol Kabupaten Tulungagung - Arifin, Firsta Putri Enjela Zainal; Maunah, Binti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to describe the efforts of social studies teachers, the form of instillation, and the results of the efforts of social studies teachers at SMP Negeri 2 Sumbergempol Tulungagung in instilling moral values in students, especially in class VII. This research uses descriptive research with a qualitative approach. The methods used in this research are participant observation, in-depth interviews, and documentation. Meanwhile, data analysis techniques use data data condensation, data display, and drawing verifying conclusions. In checking the validity of the data using extended participation, triangulation, and persistence of observation. In checking the validity of the data using extended participation, triangulation, and persistence of observation: 1) The efforts that have been conveyed by the teacher are: provide motivation and understanding of morality. Always apply dress and time discipline, It is mandatory to pray before and after studying. 2) Forms of instilling moral values that have been implemented by teachers and schools include: implementation of habituation programs such as dhuha prayers in congregation, reading the Yasin letter before learning, shaking hands with teachers, and also dhuhur prayers in congregation, madrasah diniyyah, tahsin. Apart from that, there are also activities to commemorate national holidays and Islamic holidays. 3) The results of the efforts that have been delivered and also implemented by the teacher, namely changes in students' behavioral attitudes to become better and more disciplined towards everything. Meanwhile, the results of the habituation program are: Students are more accustomed to programs that have become part of the school's culture.